Bridging theory and experiment in defect-tolerant semiconductors for photovoltaics - Hammer, Maria; Schlott, Hannah; Lüer, Larry; Brabec, Christoph; Sytnyk, Mykhailo; Will, Johannes; Meyer, Bernd; Heiß, Wolfgang (Nature Reviews Materials, 2025)
Defect tolerance is a concept applied in photovoltaics to explain semiconductors such as lead-halide perovskites that excel without relying on single-crystalline growth. It differentiates from the mere absence of defects, emphasizing on minimizing the influence of defects on minority carrier lifetimes. Whether defect tolerance is the only reason for the superiority of lead-halide-perovskite-based solution-processed solar cells is still controversial. However, the defect tolerance of various semiconductor structures and materials has been experimentally suggested and, in some cases, proven. In this Perspective, we explore defect tolerance across material science, defect characterization and computational modelling. With a primary focus on electrically or optically active defects, we systematically compare computational and experimental results from the literature. We aim to address the complexity arising from diverse theoretical approaches that have yielded partially contradictory results. Additionally, experimental findings have been subject to varied interpretations, ranging from defect signals to ion migration. We endeavour to chart a course through this intricacy and seek to establish a rigorous framework for the identification and quantitative assessment of defect toleranc

Ligand Tuning of Localized Surface Plasmon Resonances in Antimony-Doped Tin Oxide Nanocrystals - Balitskii, Olexiy; Mashkov, Oleksandr; Barabash, Anastasia; Rehm, Viktor; Afify, Hany A.; Li, Ning; Hammer, Maria; Brabec, Christoph; Eigen, Andreas; Halik, Marcus; Yarema, Olesya; Yarema, Maksym; et al. (Nanomaterials, 2022)
Aliovalent-doped metal oxide nanocrystals exhibiting localized surface plasmons (LSPRs) are applied in systems that require reflection/scattering/absorption in infrared and optical transparency in visible. Indium tin oxide (ITO) is currently leading the field, but indium resources are known to be very restricted. Antimony-doped tin oxide (ATO) is a cheap candidate to substitute the ITO, but it exhibits less advantageous electronic properties and limited control of the LSPRs. To date, LSPR tuning in ATO NCs has been achieved electrochemically and by aliovalent doping, with a significant decrease in doping efficiency with an increasing doping level. Here, we synthesize plasmonic ATO nanocrystals (NCs) via a solvothermal route and demonstrate ligand exchange to tune the LSPR energies. Attachment of ligands acting as Lewis acids and bases results in LSPR peak shifts with a doping efficiency overcoming those by aliovalent doping. Thus, this strategy is of potential interest for plasmon implementations, which are of potential interest for infrared upconversion, smart glazing, heat absorbers, or thermal barriers.
CRIS-Team WoS Importer:2022-10-28

Suppressing Nonradiative Recombination in Lead-Tin Perovskite Solar Cells through Bulk and Surface Passivation to Reduce Open Circuit Voltage Losses - Zhang, Kaicheng; Späth, Andreas; Almora, Osbel; Le Corre, Vincent Marc; Wortmann, Jonas; Zhang, Jiyun; Xie, Zhiqiang; Barabash, Anastasia; Hammer, Maria; Heumüller, Thomas; Min, Jie; Fink, Rainer; et al. (ACS Energy Letters, 2022)
Lead-Tin perovskite solar cells (Pb/Sn PSCs) are limited by the intrinsic instability of Sn(II), which tends to oxidize forming Sn vacancies in perovskite films. Herein, a Lewis base β-guanidinopropionic acid (GUA) and hydrazinium iodide (HAI) are introduced to effectively passivate the perovskite bulk and surface, respectively. The synergistic approach leads to Pb/Sn PSCs with a promising power conversion efficiency of 20.5% owing to the significantly reduced nonradiative recombination and voltage losses. As a result, the VOC × FF product of PSCs is significantly improved, which is among the highest values documented in the literature, being favorable for perovskite-based tandem applications. Additionally, the strategy demonstrated in this work could also improve the stability of PSCs by enhancing the chemical robustness of the perovskite layer. These results emphasize the significance of bulk and surface passivation in the development of efficient and stable PSCs based on Pb/Sn perovskites.
CRIS-Team Scopus Importer:2022-09-30